The Impact of Breakthrough Innovations on the Export Performance of SMEs in Developing Countries: The Moderating Role of Institutional Factors - Hashmi, Hammad Bin Azam; Voinea, Cosmina L.; Ooms, Ward; Caniëls, Marjolein C. J. (Frontiers in Psychology, 2022)
Although few studies examine the implications of breakthrough innovations in the exporting context, we have little understanding about how contingent factors in the developing countries shape the breakthrough innovations–export performance link. Thus, this study aims at examining the impact of breakthrough innovations (i.e., technology-based innovations and market-based innovations) on the export performance of SMEs in developing countries, while studying the role of contingent factors, i.e., institutional environment specificity and enforceability. The data were collected from a sample of 410 SMEs in Pakistan. Hypotheses were tested through structural equation modeling in AMOS 20. The results reveal that both technology-based and market-based innovations have a positive impact on the export performance of SMEs in terms of strategic export performance and economic export performance. Second, institutional environment specificity and enforceability enhance the impact of breakthrough innovations on the export performance of SMEs.